Trauma-focussed cognitive-behaviour therapy for people with mild intellectual disabilities: outcomes of a pilot study. Issue 5 (5th September 2016) - Stenfert Kroese, Biza; Willott, Sara; Taylor, Frances; Smith, Philippa; Graham, Ruth; Rutter, Tara; Stott, Andrew; Willner, Paul
Abstract : Purpose: Trauma-focussed cognitive-behaviour therapy (TF-CBT) is the most effective treatment for post-traumatic stress disorder (PTSD). Individuals who present with complex PTSD are among the most complex and challenging patients seen by intellectual disability psychology and psychiatry services. The purpose of this paper is to study TF-CBT intervention for people with intellectual disabilities and complex PTSD. Design/methodology/approach: Three groups of adults with intellectual disabilities (ID) presenting with complex PTSD ( n =3, n =5 and n =4) were treated using a 12-week manualised intervention adapted from a procedure routinely used in adult mental health services. Participants completed the Impact of Event Scale as adapted for people with intellectual disabilities (IES-ID) before and after the intervention, and interviews conducted to ascertain their experiences of the group were analysed using interpretative phenomenological analysis (IPA). Findings: The ten participants who completed the intervention showed a 27 per cent decrease in median Impact of Event Scale Intellectual Disabilities scores, equivalent to a medium effect size ( d =0.50). Five themes were identified from the interviews: being listened to; it is nice to know you are not the only one; being in a group can be stressful; the importance of feeling safe; achieving and maintaining change. Participants also provided constructive feedback to promote improvements to the manual. Research limitations/implications: A feasibility study followed by methodologically robust clinical trials is now needed to establish the effectiveness of the intervention and its utility in clinical practice. Practical implications: This small study has confirmed the potential of TF-CBT as an intervention for extremely vulnerable individuals with ID who present with complex PTSD. Social implications: The findings indicate that a group intervention is both feasible for and acceptable to adults with ID. Originality/value: To date, no study has investigated the effectiveness and feasibility of a TF-CBT group intervention for adults with mild ID.